Optimization of swelling and mechanical behavior of Acer platanoides cellulose combo hydrogel - Muhammad Rizwan; Sobia Naseem; Syeda Rubina Gilani; Arjumand Iqbal Durrani (Kuwait Journal of Science)
To reduce resource scarcity and environmental concerns, it is better to choose both sustainable and biodegradable materials for the synthesis of value-added products. In this study, a biodegradable combo hydrogel was developed that is prone to decompose and possesses high swello-mechanical properties. The combo hydrogel is fabricated through crosslinking of Acrylic acid (AA) and n-isopropyl acrylamide monomers on Acer platanoides cellulose (APC) in the presence of MBA (N, N-methylene bisacrylamide). The APC-combo hydrogel was characterized through SEM, FTIR, swelling, mechanical, and biodegradability tests and got results in favor. SEM images show high crosslinking density and porous surface that facilitates water penetration for swelling behavior. The potential use of cellulose in combo hydrogel helped in intensifying its mechanical and biodegradable properties. APC-combo hydrogel (APC-CH9) has a higher swelling ratio at 2:1 monomer to APC ratio, 0.5 percent MBA concentration, 70% neutralization degree, 40 °C temperature, and pH 6. Similarly, the hydrogel possesses higher values for tensile strength and Young's modulus at 0.6 percent MBA concentration but shows higher compression strength and elongation at break at 0.2% MBA. The high swello-mechanical and moderate biodegradability properties of combo hydrogel make it a promising material for minimizing the agricultural water and nutrient leaching issues and results in reducing plant wither rate.